2011
DOI: 10.1029/2011gl049589
|View full text |Cite
|
Sign up to set email alerts
|

Helium isotopes at Rungwe Volcanic Province, Tanzania, and the origin of East African Plateaux

Abstract: We report helium isotope ratios (3He/4He) of lavas and tephra of the Rungwe Volcanic Province (RVP) in southern Tanzania. Values as high as 15RA (RA = air 3He/4He) far exceed typical upper mantle values, and are the first observation of plume‐like ratios south of the Turkana Depression which separates the topographic highs of the Ethiopia and Kenya domes. The African Superplume ‐ a tilted low‐velocity seismic anomaly extending to the core‐mantle boundary beneath southern Africa – is the likely source of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 32 publications
7
50
0
Order By: Relevance
“…1b). Seismic tomography with existing sparse seismic data indicates a localized low-velocity zone in the mantle below Rungwe (O'Donnell et al, 2013), and isotopic analyses of recent volcanic rocks suggest a deep plume-influenced source, at least for the youngest magmatism (Hilton et al, 2011). However, the original cause of magmatism, the distribution of elevated temperatures and magma at depth beneath the Malawi rift, and the relationship between magmatism and extension remain unknown.…”
Section: Tectonic Backgroundmentioning
confidence: 99%
“…1b). Seismic tomography with existing sparse seismic data indicates a localized low-velocity zone in the mantle below Rungwe (O'Donnell et al, 2013), and isotopic analyses of recent volcanic rocks suggest a deep plume-influenced source, at least for the youngest magmatism (Hilton et al, 2011). However, the original cause of magmatism, the distribution of elevated temperatures and magma at depth beneath the Malawi rift, and the relationship between magmatism and extension remain unknown.…”
Section: Tectonic Backgroundmentioning
confidence: 99%
“…The second type invokes one or more plumes with plume head material ponded beneath the lithosphere fed by a narrow ($100-200 km diameter) plume tail [e.g., Green et al, 1991;Slack et al, 1994;Burke, 1996;Ebinger and Sleep, 1998;George et al, 1998;Chang and Van der Lee, 2011]. And the third grouping of models attributes the Cenozoic tectonism to a superplume [e.g., Hilton et al, 2011;Nyblade, 2011;Adams et al, 2012;Hansen et al, 2012]. If the African superplume is a through-going mantle structure then the latter type of model is obviously favored.…”
Section: Introductionmentioning
confidence: 99%
“…A superplume extending from the CMB to the surface implies an origin for the Cenozoic extension, volcanism and plateau uplift in eastern Africa rooted in the dynamics of the lower mantle (Mulibo and Nyblade 2013). Hilton et al (2011) reported helium isotope ratios of lavas and tephra of the Rungwe Volcanic Province in southern Tanzania. Values as high as 15 RA far exceed typical upper mantle values, which are attributed to the African superplume (Hilton et al 2011).…”
Section: African Hotspotsmentioning
confidence: 98%
“…Hilton et al (2011) reported helium isotope ratios of lavas and tephra of the Rungwe Volcanic Province in southern Tanzania. Values as high as 15 RA far exceed typical upper mantle values, which are attributed to the African superplume (Hilton et al 2011). Steinberger (2000) calculated the motion of hotspots in East Africa and the deformation of their underlying plume conduits using models of global mantle flow and suggested the presence of a comparatively broad upwelling rather than localized plumes.…”
Section: African Hotspotsmentioning
confidence: 98%
See 1 more Smart Citation